Maintained cerebral oxygenation during maximal self-paced exercise in elite Kenyan runners - Santos-Concejero, J.; Billaut, F.; Grobler, L.; Oliván, J.; Noakes, T. D.; Tucker, R. (Journal of Applied Physiology, 2015)
The purpose of this study was to analyze the cerebral oxygenation response to maximal self-paced and incremental exercise in elite Kenyan runners from the Kalenjin tribe. On two separate occasions, 15 elite Kenyan distance runners completed a 5-km time trial (TT) and a peak treadmill speed test (PTS). Changes in cerebral oxygenation were monitored via near-infrared spectroscopy through concentration changes in oxy- and deoxyhemoglobin (Delta[O2Hb] and Delta[HHb]), tissue oxygenation index (TOI), and total hemoglobin index (nTHI). During the 5-km TT (15.2 ± 0.2 min), cerebral oxygenation increased over the first half (increased Delta[O2Hb] and Delta[HHb]) and, thereafter, Delta[O2Hb] remained constant (effect size, ES = 0.33, small effect), whereas Delta[HHb] increased until the end of the trial (P < 0.05, ES = 3.13, large effect). In contrast, during the PTS, from the speed corresponding to the second ventilatory threshold, Delta[O2Hb] decreased (P < 0.05, ES = 1.51, large effect), whereas Delta[HHb] continued to increase progressively until exhaustion (P < 0.05, ES = 1.22, large effect). Last, the TOI was higher during the PTS than during the 5-km TT (P < 0.001, ES = 3.08; very large effect), whereas nTHI values were lower (P < 0.001, ES = 2.36, large effect). This study shows that Kenyan runners from the Kalenjin tribe are able to maintain their cerebral oxygenation within a stable range during a self-paced maximal 5-km time trial, but not during an incremental maximal test. This may contribute to their long-distance running success.